Development of ethnoscience-oriented multimedia learning salt manufacturing process from conductivity materials - Suryani, Dewi; Yasir, Mochammad; Sidik, Rahmad Fajar (IAIN Palangka Raya, 2023)
The purpose of this study was to obtain an ethnoscience study of conductivity material and to determine student responses to media. This research uses a descriptive qualitative method with the ADDIE development model. The research location is in one of the salt ponds in Bangkalan Regency and SMP Negeri 2 Kamal. The sampling method was a simple random sampling of as many as 10 students of class VII. Data collection techniques using interviews, questionnaires, and documentation. The percentage of student responses on the display aspect is 97.33% and the material aspect is 94.25% which is included in the very positive criteria.